O desenvolvimento profissional dos professores de escolas da rede pública estadual do município São Cristóvão/SE - Santos, Claúdia Patrícia Melo Marinho (2023)
The teacher training process is complex and full of nuances that require reflection and investigative analysis. In this field of teacher training, many studies have deepened discussions on the study of teacher professional development. The general objective of this research was to investigate the factors that influence the professional development of teachers in the public school system in the municipality of São Cristóvão, based on the organizational and personal dimensions of the teacher. The research is qualitative in nature and in terms of its objectives it is defined as descriptive research. To collect the data, a questionnaire was used to identify the profile of the research participants and what they said about their professional development, and an interview was conducted with the school coordinators. Data analysis was based on content analysis, with the information obtained being treated and categorized. The participants in the research were elementary school, high school and youth and adult education teachers from the municipality of São Cristóvão/SE, specifically from the Rosa Elze neighborhood, comprising a total of six schools. The results obtained indicate that the organizational factors that most influence teachers' professional development are the low supply or absence of training courses in teachers' areas of interest, the physical conditions and access to the courses on offer and the quality of the continuing training and their trainers. In the personal dimension, the greatest influences on professional development are related to family issues, time to dedicate to training and motivation to get involved in development processes. This research contributes to the field of teacher training, the state education system in Sergipe and other education systems, as it could become a parameter for future research.